2012
DOI: 10.1080/17686733.2012.743697
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional (3D) inverse heat flux evaluation based on infrared thermography

Abstract: Inverse methods in heat transfer are generally associated with the estimation of unknown heat fluxes on inaccessible surfaces, based on temperature measurements performed on the accessible walls. In the present application, an inverse heat conduction method was developed that uses temperature measurements performed by infrared thermography. The threedimensional (3D) transient inverse heat transfer problem was solved by using an iterative regularisation with a conjugate gradient method. The inverse solver was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Both results showed very limited dependence on transverse conduction. Other authors (Nortershauser and Millan 2000;Sousa et al 2012) have performed 3D-IHCP solutions on problems considering the heating of small test articles by flames and electric heaters, but they only considered relatively small computational domains (approximately 300 cells). In the case of the present work, any assumptions of 1D or 2D conduction cannot be made-the conduction in the model near the corners and edges will be strongly two or three-dimensional and therefore the 3D-IHCP solution must be solved.…”
Section: Hypersonic Heat Flux Calculationmentioning
confidence: 99%
“…Both results showed very limited dependence on transverse conduction. Other authors (Nortershauser and Millan 2000;Sousa et al 2012) have performed 3D-IHCP solutions on problems considering the heating of small test articles by flames and electric heaters, but they only considered relatively small computational domains (approximately 300 cells). In the case of the present work, any assumptions of 1D or 2D conduction cannot be made-the conduction in the model near the corners and edges will be strongly two or three-dimensional and therefore the 3D-IHCP solution must be solved.…”
Section: Hypersonic Heat Flux Calculationmentioning
confidence: 99%
“…Some general aspects in solving inverse heat conduction problems in IR thermography were considered by Papini [58]. Recently, Sousa et al suggested a solution to the 3D transient inverse problem using an iterative regularization with a conjugate gradient method [59]. Kouadio et al described a new robust algorithm for the estimation of thermal diffusivity, which is based on a loworder weak formulation method of the heat conduction equation using a virtual test function [60].…”
Section: Inverse Tndt Problems and Defect Characterizationmentioning
confidence: 99%
“….しかし,PIV と LIF の蛍光染料の選択肢の制限や蛍光染料の温度の時間分解能・応答といった観点から,非定常熱流動場の同時 計測には課題が残る.一方,赤外線カメラの性能が近年飛躍的に向上しており,高い時間・空間分解能,及び高 in the Near-Wall Region Using High-Speed Infrared Thermography and PIV い温度分解能を有する高速赤外線カメラが開発されている.赤外線カメラによる計測では,2 次元の多点温度計 測が可能であり,通電加熱金属箔上の衝突噴流や,縦渦による膜冷却に関する温度計測に用いられている (7) .ま た,伝熱面裏面の温度から逆解析により熱伝達率を推定する手法が提案されている (8) . これまで非定常な対流熱伝達の時空間分布を実測する方法として,中村は通電加熱金属箔上の温度分布を赤外 線カメラで測定して瞬時・局所の熱伝達率を算出する方法を提案し,乱流境界層における熱伝達率の時空間分布 を定量的に測定した (9) .また,同様に後向きステップ流れの測定を実施し,はく離・再付着流れに伴う熱伝達率 の時空間分布を報告した (10) 3・4 赤外線カメラによる温度計測と熱伝導方程式の逆解析…”
unclassified